Peningkatan Hasil Padi (Oryza sativa L.) dan Kadar Zink dalam Beras melalui Aplikasi Zink Sulfat Heptahidrat - Hamam, Maulana; Pujiasmanto, Bambang; Supriyono, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Zinc is an essential micro-nutrients for humans and plants. Zinc on humans is obtained from food, especially rice. This research studied the effect of zinc sulfate heptahydrate spraying application, the effect of zinc sulphate heptahydrate enriched urea application, and the interaction of both, on yield and rice zinc grain concentration in Ciherang varieties. The research was carried out by RCBD. The first factor was without spraying zinc sulfate, spraying 75 g ha-1 zinc sulfate heptahydrate and spraying 150 g ha-1 zinc sulfate heptahydrate. The second factor was without zinc sulfate enriched urea, urea enriched by 7.5 kg ha-1 zinc sulfate heptahydrate, and urea enriched by 15 kg ha-1 zinc sulfate heptahydrate. The parameters observed were grain yield, grain zinc concentration, and rice plant growth. Data were analyzed by analysis of variance at 5% and DMRT test at 5%. The results indicated that spraying 75 g ha-1 zinc sulfate heptahydrate increased yield of rice up to 13%, urea enriched by 7.5 kg ha-1 zinc sulfate heptahydrate increased grain yield zinc concentration up to 33%, Combination of spraying  75 g ha-1 zinc sulfate heptahydrate and urea enriched by 7.5 kg ha-1 zinc sulfate heptahydrate can’t increased the yield and zinc grain concentration.Keywords: rice, urea, zinc, zinc sulfate heptahydrate